Severe flea infestation in dairy calves - Dryden, Michael W.; Broce, A. B. (Kansas Agricultural Experiment Station, 2011)
In June 1991, an investigation was conducted of a severe flea infestation in 23 Holstein dairy calves in South Central Kansas. Inspection of the dairy revealed massive numbers of fleas on calves and in the barn where they were housed. Analysis of blood samples from 10 calves revealed that nine of them had mild to severe anemia. A management program was initiated consisting of treatments of calves and premises with insecticide and insect growth regulator and removal of straw bedding from the barn. Inspection of the dairy 9 wk after this complete control program was initiated revealed that fleas were not evident on calves or on the premises.
Keywords: Dairy; Calves; Fleas; Methoprene; Anemia